A study of the distribution of the macrobiota of the Aganan River, Alimodian, Iloilo - Amparado, Edna A. (Iloilo University of the Philippines System, College Iloilo, 1978)
The paper is a study on the distribution of the macrobiota of the Aganan River in Alimodian, Iloilo. Studies were conducted on February 2-6, 1978 to investigate specifically the effects of substratum and current velocity the distribution of the macrobiota. The study area was divided into five stations ; each measured fifty meters long and traversed the whole width of the stream. Animal life was an assemblage of insects, frogs, toads, minnows, snails and prawns. Insects, the dominant macro-consumers were represented by Orders Ephemeroptera, Coleoptera, Dptera, Hemiptera and Trichoptera. Mayflynymphs of Order Ephemeroptera, the most abundat macroconsumers lved under the stones of the rapids. The musk grasses which ae green algae, water mosses and digman were the autotrophs of the stations. Current velocity and substratum quality influenced the distribution of the macrobiota. Current velocity and substratum quality influenced the distribution of the macrobiota. Current imposed limitations on the maintenance of position and affected the degree of light penetration. Substratum limited the distribution of the macrobiota as a consequence of its abrasiveness, smothering action and instability. Based on the results of the study it is recommended that a twelve-month period of observation be undertaken and that stations should also be established on barrios along the routes of the iver, To minimize effects that might be caused by differences in the abiotic conditions, simultaneous ecological surveys of all tha stations be made. This could be done by a group of 5-6 student working on a particular station. It is further recommended that planktons and study of abiotic factors like ph, temperature, dissolved oxygen and turbidity be included.
Research Paper (M.A. in Teaching Biology). -- Iloilo City : U.P. College Iloilo, November 1978.
Keywords: Aganan River -- Alimodian, Iloilo